The Effect of the Instrumental Enrichment Strategy on Acquiring Geographical Concepts for Second Intermediate Grade Learners - Najm, Muthana Abdullah; Azw, Abd Al-hamid (Journal of Tikrit University for Humanities, 2023)
The experimental technique was used to determine how instrumental enrichment affects second intermediate graders’ spatial concept acquisition. The study sample was confined to Kirkuk governorate schools and Al-Hamza bin Abdul-Muttalib Middle School for Boys, with a student population of The sample (63) students was divided into two groups: an experimental group of (32) students who were taught the subject using the methodical enrichment strategy, and a control group of (31) students who were taught using the traditional method. The research tool was a multiple-choice achievement test. The following results were obtained: Statistically significant differences were seen at a significance level of 0.05 in the mean scores of the concept acquisition test for the experimental group and the control group. These differences were observed at each level of definition and differentiation. Following the implementation of the enrichment technique, the experimental group emerged as the victor. The experimental group’s learning of spatial concepts (definition, discrimination, application) was significantly influenced by the implementation of the instrumental enrichment approach, with an effect of 0.90.